ON ESTIMATED ACCURACY OF PART CUTTING UNDER MACHINE INTELLIGENT CONTROL - Alexey Fedorovich Lysenko; Andrey Igorevich Izyumov; Oleg Valentinovich Goncharov (Advanced Engineering Research, 2014)
The effect of different methods of accounting error components of the engineering system on the treatment process to achieve the desired product quality is considered. The feasibility of the inherited and operational characteristic control based on the intelligent control systems is described. The technique of the part squareness estimate is offered. The novelty of the approach is in analyzing the effect of the combined characteristics that is more informative versus the effect estimate of each of them. An algorithm for the function calculation program of distributing the cutterpath coordinates used to evaluate entering the acceptable range is presented. An example of the probable error calculation procedure application including the effect of deviation of the tool actual trajectory from the CNC programmed one under part cutting on the multi-operation machine is provided.